Effects of Energy-Protein Balance in the Diet on Semen Characteristic of West Java Local Ducks - H. S., Siti Wahyuni; Setiawan, Rangga; Sujana, Endang (KnE Life Sciences, 2017)
Cihateup (West Java highland) and Rambon (West Java lowland) ducks are two local ducks which are commonly raised by farmers in West Java under extensive systems. The decline of land availability as a result of increasing human population has meant that the ducks should be raised under intensive system. An experimental research was conducted to evaluate the effect of energy-protein balance in the diet on semen characteristic of Cihateup and Rambon drakes under restricted water system (intensive system). The research was designed in Completely Randomized Design; there were six energy-protein balance in the diets as treatment, which were G1 ( 3000 kcal/kg ME, 20 % CP); G2 ( 3000 kcal/kg ME, 16 % CP); G3 ( 3000 kcal/kg ME, 13.5% CP); G4 (2700 kcal/kg ME, 20 % CP); G5 (2700 kcal/kg ME, 16 % CP); and G6 ( 2700 kcal/kg ME, 13.5 % CP); each treatment was replicated three times. Semen was collected when the drakes reached the age of nine months and semen evaluation for volume semen, sperm motility and sperm abnormality was conducted. The results show that semen characteristics show that the highest motility was produced by G5 (2700 kcal/kg ME, 16 % CP) for Cihateup drakes and G6 ( 2700 kcal/kg ME, 13.5 % CP) for Rambon drakes. There was no significant different effect among treatments on abnormality of Cihateup drakes semen; anyhow G5 (2700 kcal/kg ME, 16 % CP) can be considered as the best diet for Rambon drakes based on its semen abnormality. It can be concluded that at feeding diet containing similar Metabolizable Energy level, Cihateup drakes required higher protein level than Rambon drakes to produce a good quality of semen. Keywords: energy-protein balance, west java local drakes, semen